Outcomes of Right Ventricular Outflow Tract Stenting as a Palliative Procedure in Tetralogy of Fallot Patients - Pickup, Victoria; Joshi, Jayneel (SA Heart Journal, 2024)
Background: Certain groups of tetralogy of Fallot (TOF) patients require a palliative procedure until factors permit a full surgical repair. An aorto-pulmonary shunt is the gold standard palliative procedure but requires a cardiothoracic surgeon in a well-equipped facility. In the government sector in a developing country this limited resource has an overwhelming caseload. Right ventricular outflow tract (RVOT) stenting via cardiac catheterization by a trained paediatric cardiologist is a possible alternative. Objectives: To demonstrate that RVOT stenting is a safe and effective palliative procedure in TOF patients in a resource limited setting. Method: A retrospective, cohort observational study at Steve Biko Academic Hospital from January 2014 to March 2021. Results: 37 patients required RVOT stent placement. Mean oxygen saturation increased from 65% to 95% post-stent insertion. Mean pulmonary artery (PA) growth, measured by McGoon ratio, increased from 1.36 to 2.05. Average Intensive Care Unit stay was 2 days with a zero 30-day mortality. Three stents fractured requiring replacement. Conclusion: Stenting the RVOT in TOF patients who present at an older age, with multiple comorbidities and often in extremis, has yielded good results. Significant improvement in oxygen saturations and PA growth permits majority of our patients to a full TOF surgical repair.